Impact of exposure of crude oil and dispersant (Corexit) on aggregation of extracellular polymeric substances - Chiu, Meng-Hsuen; Vazquez, Carlos I.; Shiu, Ruei-Feng; Le, Clarence; Sanchez, Nicole R.; Kagiri, Agnes; Garcia, Cynthia A.; Nguyen, Chanh H.; Tsai, Shih-Ming; Zhang, Saijin; Xu, Chen; Santschi, Peter H.; et al. (The Science of the total environment, 2019)
Spilled oil treated with Corexit dispersant can cause unintended impacts on marine environment systems including altering marine organic matter dynamics; however, impacts on microgels and marine oil snow (MOS) formation are still debated and remain to be fully understood. Extracellular polymeric substances (EPS) are a major source of marine organic carbon for MOS and microgel formation. EPS initial aggregation plays key roles in the oil degrading process and various biogeochemical reactions. Here we used four types of EPS with water accommodated fraction (WAF), chemically-enhanced WAF (CEWAF) and Corexit, to represent potential situations during oil spills and post-application of Corexit. We found that Corexit alone can inhibit EPS aggregation and disperse pre-existing microgels. CEWAF can enhance EPS aggregation with efficiency by up to 80%–100% and more aggregates accumulated within the air-water interface. Additionally, more hydrophobic EPS aggregates showed high resistance to Corexit dispersion while hydrophilic EPS were more sensitive. Effects of oil spills on marine gel particle formation are primarily determined by chemical characteristics (hydrophobicity and protein content) of the constituent EPS. This study offers unique insights for organic particle dynamics and identifies controlling factors for MOS or gel particles associated with oil spills and Corexit dispersant used. [Display omitted] •Corexit alone can inhibit EPS (extracellular polymeric substances) aggregation.•Pre-existing EPS microgels can be dispersed by Corexit.•Chemically-enhanced water accommodated fraction can enhance EPS aggregate formation.•Hydrophobic EPS aggregates showed more resistance to Corexit dispersion.•Hydrophobicity and protein content play key role in EPS behavior.